Association between Human Papillomavirus 16 Viral Load in Pregnancy and Preterm Birth - Pranamika Khayargoli; Marie-Hélène Mayrand; Joseph Niyibizi; François Audibert; Louise Laporte; Julie Lacaille; Ana Maria Carceller; Jacques Lacroix; Émilie Comète; François Coutlée; Helen Trottier (Viruses, 2024)
Recent evidence shows increased preterm birth risk with human papillomavirus-16 (HPV16) infection during pregnancy. This study aimed to measure the association between HPV16 viral load during pregnancy and preterm birth. We used data from participants in the HERITAGE study. The Linear Array assay was used for HPV DNA testing on vaginal samples collected during the first and third trimesters of pregnancy. The HPV16 viral load was measured with a real-time polymerase chain reaction. We used logistic regression to measure the associations between HPV16 viral load during pregnancy and preterm birth (defined as birth before 37 weeks of gestation). The adjusted odd ratios (aORs) and the 95% confidence intervals [CIs] were estimated with inverse probability treatment weighting of the propensity score. This study included 48 participants who tested positive for HPV16 during the first trimester of pregnancy. The aOR for the association between first-trimester HPV16 viral load (higher viral load categorized with a cutoff of 0.5 copy/cell) was 13.04 [95% CI: 1.58–107.57]). Similar associations were found using different cutoffs for the categorization of viral load during the first and third trimesters. Our findings suggest a strong association between a high HPV16 viral load during pregnancy and preterm birth, demonstrating a biological gradient that reinforces the biological plausibility of a causal association.